Answer:
n - (-6) < 9
n < 3
Step-by-step explanation:
When setting up an inequality, using the key words from the problem will help. The word 'difference' would indicate subtraction and 'less than' would be the '<' inequality sign. Since the expression is 'the difference of a number and -6', we write:
n - (-6) < 9
Whenever we subtract a negative number, we change both signs to positive:
n + 6 < 9
Using inverse operations to solve: n + 6 - 6 < 9 - 6
n < 3
It would be 3/5 because if you simplify it you would bet 3/5
Y would be 16,
y=kx
6=3k
2=k
y=2(8)
y=16
Answer:
so y.u on it lollllll
Step-by-step explanation:
bro you hat brainly for wut